The Effect of Green Accounting, Profitability, and Leverage on Corporate Financial Performance - Nimas Utari, Hanung Ratri; Affandy, Didied Poernawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Environmental degradation, climate change, and issues related to sustainability are major challenges pressing companies in all parts of the world, especially Indonesia. The existence of this challenge proves that an accounting system that incorporates environmental evaluation, such as green accounting, is needed. This study aims to analyze, identify, and empirically prove the effect of green accounting, profitability, and leverage on the financial performance of basic materials, industrials, and consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. The data of this study are analyzed by panel data regression processed by Eviews 13 software, and the results exhibit that green accounting and leverage have a positive and insignificant effect on the companies’ financial performance, and profitability has a positive and significant effect on financial performance. This study recommends that companies maintain their profitability to result in good financial performance, and serves as an insight and reference for further research especially on financial performance.